EFEKTIVITASILODALAM MENJALANKAN MY-PECTAHUN 2014-2017DITINJAU DARI VARIABEL STRUKTURAL - Prameita Yastini, Made Dwi; Putri, Penny Kurnia; Parameswari, A.A. Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT Myanmar is a small economy country with a high number of child laborers. The chronic problem of child labor gain major concern from ILO. As a United Nations agency, ILO established a program entitled